Shale lithofacies controls on porosity and pore structure: An example from Ordovician Goldwyer Formation, Canning Basin, Western Australia - Iqbal, Muhammad Atif; Rezaee, Reza; Smith, Gregory; Ekundayo, Jamiu (ELSEVIER SCI LTD, 2021)
The hydrocarbon storage and transport capacity of shale reservoirs are dependent on its complex pore systems. This study focuses on Ordovician Goldwyer Formation (Goldwyer shale) from Canning Basin, Western Australia. Multi-scale qualitative (X-ray diffraction, field emission scanning electron microscope, TESCAN integrated mineral analyser (TIMA) and thin-section analysis) and quantitative (Rock-Eval® pyrolysis, helium porosity on crushed samples, low-pressure gas adsorptions (N2 and CO2) and mercury injection capillary pressure (MICP)) approaches were applied on shale samples. The results indicate that the Goldwyer shale comprises five main lithofacies (namely organic-rich shale, argillaceous shale, siliceous shale, calcareous shale, and mixed shale) based on mineral composition and total organic carbon (TOC) content. The organic-rich and siliceous shales have highest porosity (>10%) followed by mixed shale and other lithofacies. Three types of pores, namely organic pores, interparticle, and intraparticle pores, are identified in Goldwyer shale. Most of the pores are narrow slit-like or bottle-necked shaped pores. The micropore and mesopore volumes and specific surface area (SSA) of all lithofacies are positively related to TOC except for the argillaceous shale. Conversely, the micro and mesopore parameters (SSA and pore volumes) exhibited inverse relations with total clay content for all lithofacies except argillaceous shale. This indicates that the total clay and TOC content is the main controlling factors for pore structure of Goldwyer shale. The whole pore aperture exposed that mesopores are more abundant in Goldwyer shale; however, few micro and macropores are also found in different lithofacies. The organic-rich, siliceous and mixed shales could be deemed as the most essential lithofacies types for fluid flow via pore systems due to high porosity and feasible pore structures.